2020
DOI: 10.1111/jcmm.15671
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV attenuates inflammatory response mediated by NLRP‐3/calpain‐1 is involved in the development of pulmonary hypertension

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 11 publications
2
16
0
Order By: Relevance
“…Consistent with our findings, a recent study demonstrated that AS-IV reduced blood pressure in rats fed with a high-fat diet [33]. AS-IV has been also found to attenuate pulmonary artery pressure induced by hypoxia or monocrotaline as well as pulmonary artery structural remodeling [25,26,34,35]. The decrease in blood pressure can be associated with vascular relaxation mediated by AS-IV.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our findings, a recent study demonstrated that AS-IV reduced blood pressure in rats fed with a high-fat diet [33]. AS-IV has been also found to attenuate pulmonary artery pressure induced by hypoxia or monocrotaline as well as pulmonary artery structural remodeling [25,26,34,35]. The decrease in blood pressure can be associated with vascular relaxation mediated by AS-IV.…”
Section: Discussionsupporting
confidence: 91%
“…Inflammation plays an important role in the development of pulmonary vascular remodelling [ 16 , 17 ]. Several studies have demonstrated that the NLRP3 inflammasome and IL-1β play a pivotal role in the pathogenesis of PAH induced by MCT [ 19 21 ]. Our study found that the expression of the NLRP3 inflammasome increased and the levels of IL-1β and IL-18 in plasma were higher in vehicle-treated MCT rats than in rats in the control group, which is in accordance with the results of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…AS-IV decreases the protein expression levels of NLRP3, caspase-1, ASC, IL-18, IL-1β and calpain-1 in vivo and/or in vitro in a pulmonary hypertension model (Sun et al. 2021 ).…”
Section: Discussionmentioning
confidence: 99%